2005
DOI: 10.1038/nature435755a
|View full text |Cite
|
Sign up to set email alerts
|

Red tides and marine mammal mortalities

Abstract: Potent marine neurotoxins known as brevetoxins are produced by the 'red tide' dinoflagellate Karenia brevis. They kill large numbers of fish and cause illness in humans who ingest toxic filter-feeding shellfish or inhale toxic aerosols 1 . The toxins are also suspected of having been involved in events in which many manatees and dolphins died, but this has usually not been verified owing to limited confirmation of toxin exposure, unexplained intoxication mechanisms and complicating pathologies 2-4 . Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
291
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(298 citation statements)
references
References 5 publications
4
291
2
1
Order By: Relevance
“…Brevetoxins can lead to human health concerns through the consumption of shellfish contaminated by accumulated brevetoxins, known as neurological shellfish poisoning, or through reduced respiratory function from aerosolized brevetoxins in sea spray (1,3,4). In addition, K. brevis blooms have led to massive fish kills and compromise sea turtle, sea bird, and marine mammal health, playing a major role in the ecology of the Gulf of Mexico (1,5).…”
mentioning
confidence: 99%
“…Brevetoxins can lead to human health concerns through the consumption of shellfish contaminated by accumulated brevetoxins, known as neurological shellfish poisoning, or through reduced respiratory function from aerosolized brevetoxins in sea spray (1,3,4). In addition, K. brevis blooms have led to massive fish kills and compromise sea turtle, sea bird, and marine mammal health, playing a major role in the ecology of the Gulf of Mexico (1,5).…”
mentioning
confidence: 99%
“…In humans, brevetoxins cause neurotoxic shellfish poisoning, and brevetoxin-contaminated aerosols cause respiratory irritation and illness (2, 5). Blooms also cause massive fish kills (6), as well as bird and marine mammal mortalities (7,8). In 2005, a bloom of K. brevis lasted for more than a year and caused extensive mortalities at all trophic levels in lagoons, coastal ecosystems, and offshore reefs on the west Florida shelf (8, 9).…”
mentioning
confidence: 99%
“…In theory, even human mortalities could result from neurotoxic shellfish poisoning (NSP), although no mortalities have yet been linked conclusively to this source (Fleming et al 2011). FRTassociated mortalities have been observed in marine mammals, however, including manatees and oceanic dolphins, and also in sea turtles, seabirds, and finfish (Flewelling et al 2005, Landsberg et al 2009, Fire and Van Dolah 2012, Capper et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Kirkpatrick et al (2010) found ED visits for digestive illnesses at the Sarasota Memorial Hospital increased by 40% during an FRT bloom event in 2001 (0.07 ± 0.01 per 100,000 cases) relative to 2002 (0.05 ± 0.01 per 100,000 cases) when there was no FRT bloom. Although shellfish harvest areas (SHAs) typically were closed during FRT blooms to mitigate the risks of NSP from the consumption of molluscan bivalves, these authors argued that humans could be contracting digestive illnesses through other pathways, including the consumption of illegally harvested shellfish, whole finfish (especially the entrails, where brevetoxins may be concentrated), the breathing of aerosols contaminated with brevetoxins, or the inadvertent swallowing of contaminated seawater (Flewelling et al 2005). …”
Section: Introductionmentioning
confidence: 99%